EKSISTENSI LEMBAGA MUKIM DALAM PENERAPAN SYARI’AT ISLAM DI ACEH - Zul Azimi (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2015)
Mukim Institution has contributed greatly in coloring people's lives Acehto implement Islamic law. This institution has existed since before independenceand after independence. The existence of Mukim Institution has undergone variouschanges in policy. One of the policies of the board remove Kav occurred duringthe New Order. As for the causes, because the rules are applied. No. 5 of 1979 onVillage Government. The aim is to standardize the rules across the form andstructure of local institutions with national pattern for the realization of Pancasilademocracy. As a result, all local institutions in areas of Indonesia does not work,including the Mukim Institution in Aceh. While existing rules, but the existence ofinstitutions Kav still get a special place in the hearts of the people. The proof canbe seen in the inclusion of sub-district in the affairs of society, both in landdisputes, domestic conflict, as well as a violation of Islamic law. Many issues canbe resolved Reuters facilitated with dignity. On this basis, the government agencyReuters revitalized by applying Qanun No. 4 of 2003 concerning the Governmentof Mukim. The Canon authorizes the agency Mukim to apply Islamic law,preserving the customs and duty of the government. At this time the board had aminimal role in Pidie District. As a result, the increasing violations of Islamic law,the implementation of the teachings of Islam began to decline and customs beginto disappear. documentation. Factors causing the increase in violations of Islamiclaw in Aceh because the agency Mukim less participate. To restore the dignity ofthis institution should get serious attention from the government of Pidie andAceh. Revitalization strategy will be realized by giving full authority,socialization qanun, enabling all devices work and provide facilities to the agencyMukim.